Influence of Fiber Blending on Thermal and Acoustic Properties Nonwoven Material. Issue 15 (23rd November 2022) - Boominathan, Senthilkumar; Bhuvaneshwari, M.; Sangeetha, K.; Pachiyappan, K.M.; Devaki, E
ABSTRACT: Natural fibers are sustainable and biodegradable for acoustic product manufacturing. The natural fibers-based nonwoven textiles are utilized as cost-effective soundproof materials. This paper investigated the sound absorption properties of needle punched nonwoven fabric made from natural fibers such as Sansevieria stuckyi, Banana, Hemp, and its blends. All the raw fibers were extracted from the source plant. Twelve different needle-punched non-woven fabrics were produced using blended and non-blended fiber combinations. The investigation was carried out with the sound wave frequencies ranging from 0 Hz to 4000 Hz through the impedance tube method. The important research findings are that the blended fiber-based nonwoven mat yields a maximum sound absorption coefficient than the nonwoven mat produced with mono fibers. Higher hemp fiber proportion and higher nonwoven thickness have yield maximum sound absorption coefficient. SEM analysis was carried out to understand the surface morphologies extracted fibers. The Air permeability, porosity, and thermal conductivity of the nonwoven fabric influenced the sound absorption properties.